The Strategic Role of The Implementation of Financial Literacy Education For Early Childhood - Sulistyowati, Umi Fadhilah; Suryanto, Suryanto (CV. Publikasi Indonesia, 2025)
The importance of financial literacy education has increased as modern economies grow more complex, yet its implementation in Indonesia—particularly at the early childhood level—remains inadequate. Families often overlook the necessity of teaching children about finances, and schools have not fully integrated financial literacy into formal curricula. This study aims to examine the strategic role of early childhood financial literacy education and propose an effective framework involving both family and school environments. A qualitative-descriptive method was applied, supported by literature review and conceptual analysis, to explore how values of financial literacy can be instilled in children from an early age. The findings reveal that families serve as the primary environment for nurturing financial behavior, while schools play a complementary and reinforcing role. Effective financial education requires alignment between parental practices and structured curriculum supported by trained educators. The study highlights that integrating financial literacy early leads to more responsible financial behavior in adulthood and contributes to national goals of economic resilience and inclusion. It recommends policy integration, curriculum reform, and parent-teacher collaboration as core strategies. This research serves as a foundation for building inclusive financial education models tailored to developing countries.